Minors in the entertainment industry: the need for a comprehensive guideline in Malaysia / Nurfadhilah Che Amani and Dina Imam Supaat - Che Amani, Nurfadhilah; Imam Supaat, Dina (2014)
Child exploitation and manipulation in the entertainment industry are occurring in all parts of the world. Without express legal protection, working children in developed and developing countries alike are at risks of being poorly treated and denied the enjoyment of their basic rights. The purpose of this study is to show that there are serious justifications to persuade the Malaysian authority to better regulate children’s involvement in the show business. It also demonstrates that the protection of minors in the entertainment industry should be guided by the principle of the best interest of the child. In line with the guiding principles of the United Nation Convention on the Rights of the Child and the Islamic point of view, this study suggests that a comprehensive guideline should be established. Reference to existing guidelines in other jurisdictions and the proposed key contents of the guidelines are also highlighted in this article.